A New Evaluation Method for Groundwater Quality Applied in Guangzhou Region, China: Using Fuzzy Method Combining Toxicity Index. (1st February 2016) - Liu, Fan; Huang, Guanxing; Sun, Jichao; Jing, Jihong; Zhang, Ying
ABSTRACT: : Groundwater quality assessment is essential for drinking from a security point of view. In this paper, a new evaluation method called toxicity combined fuzzy evaluation (TCFE) has been put forward, which is based on the fuzzy synthetic evaluation (FSE) method and the toxicity data from Agency for Toxic Substances and Disease Registry. The comparison of TCFE and FSE in the groundwater quality assessment of Guangzhou region also has been done. The assessment results are divided into 5 water quality levels; level I is the best while level V is the worst. Results indicate that the proportion of level I, level II, and level III used by the FSE method was 69.33% in total. By contrast, this proportion rose to 81.33% after applying the TCFE method. In addition, 66.7% of level IV samples in the FSE method became level I (50%), level II (25%), and level III (25%) in the TCFE method and 29.41% of level V samples became level I (50%) and level III (50%). This trend was caused by the weight change after the combination of toxicity index. By analyzing the changes of different indicators' weight, it could be concluded that the better‐changed samples mainly exceeded the corresponding standards of regular indicators and the deteriorated samples mainly exceeded the corresponding standards of toxic indicators. The comparison between the two results revealed that the TCFE method could represent the health implications of toxic indicators reasonably. As a result, the TCFE method is more scientific in view of drinking safety.